Effects of Self-Efficacy on Students’ Academic Performance - Alay Ahmad Triantoro Safaria (Journal of Educational, Health and Community Psychology, 2013)
AbstractEarlier studies show an effect of self-efficacy on students’ learning and achievement. Self-efficacy has operationally defined as one’s belief that people can successfully perform a given task. The main purpose of the paper is to discuss how self-efficacy developed and the way it influences students’ academic performance in addition to social interaction with peers. A scenario was given to Pakistani high school students by solving mathematical problems. Present study was designed to study the impact of self-efficacy on 15 boys, students of the 5th grade of a local school. Hague’s (1990) Urdu Self-efficacy scale was administered. It was found that students with high self-efficacy obtained higher scores on 50 mathematical problems test. Further, content analysis of interviewees’ responses showed that students with high self-efficacy planned to study complex subjects in future. A cross-cultural study is strongly recommended in this issue that determines the students’ future.Keyword: Self-efficacy, mathematical problems, Pakistani students, complex course.